The G20 at the Cancun Ministerial : developing countries and their evolving coalitions in the WTO - Narlikar, Amrita (2004)
Seeks to determine how developing country coalitions at Cancun managed to preserve such high levels of cohesion, when many other such coalitions in the past had failed.